E-010 Cerebral venous navigation under coregistered fluoroscopy and mr angiography. technical note. (23rd July 2017) - BLANC, R; Fahed, R; Smajda, S; Redjem, H; Desilles, J; Roux, P; Mazighi, M; Ciccio, G; Piotin, M
Abstract : Introduction: Venous access is being increasingly used for the endovascular treatment of many cerebrovascular diseases (Intracranial hypertension, dural cavernous fistulas, Arteriovenous malformations). Venous roadmapping through arterial injection can be problematic because of contrast media dilution and slow flow velocity leading to moderate quality of veins visualization or necessity to repeat injections. Live 3D roadmapping is an image-processing technique which allows dynamic vessels roadmapping which immediately adapts to the C-arm movements without the need for any contrast medium injection. This technique involves the coregistration of a previously obtained magnetic resonance angiography with live fluoroscopy in order to create a combined roadmap of the vessels. Objective: To report our preliminary experience with Vessel navigator (Philips, Best, the Netherlands) for guidance of endovascular venous procedures at the intracranial level.Results After semi automatic coregistration, live 3D roadmapping of the 3D MR venography overlaid on the live fluoroscopy images was used for cases of Venous pressure measurement, intracranial venous stenting and arteriovenous dural malformations endovascular treatments. Conclusion: Our preliminary experience suggests that it is a feasible and safe technique for venous navigation and performance of and for intracranial venous procedures from the jugular vein to the intracranial sinuses. The accuracy of the coregistration is satisfactory. The potential to lower overall radiation dose and contrast medium use needs to be verified with further studies. Disclosures: R. Blanc: None. R. Fahed: None. S. Smajda: None. H. Redjem: None. J. Desilles: None. P. Roux: None. M. Mazighi: None. G. Ciccio: None. M. Piotin: None.